FINANCING TRENDS OF TRADE AND LOGISTICS SECTOR IN DEVELOPING COUNTRIES: THE CASE OF AZERBAIJAN - Ayaz Museyibov; Ayhan Satiji (Economy and Sociology)
The banking sector of Azerbaijan plays an important role in the stimulation of the economic development with a special accent to the sphere of the trade and logistics. This study touches on how the area augments economic growth largely through the adoption of the smart governmental interventions with the integration of digital advancements. Applying the mixed-method approach, which entails both qualitative and quantitative research techniques, and taking data ranging from 2010 to 2022 from State Statistical Committee of Azerbaijan, World Bank and other financial reports and documents, the study set out to reveal main financial flows in sectors of overall economy of Azerbaijan. It tests the banking sector's finiding through the calculation of amount loaned to GDP, prudential lending with the ability to identify risks and thus contribute to the stability of the financial system and the subsidization of some financial services, especially in the rural areas. The evaluation follows this up with an assessment of the performance of the private sector financing in this context, and how once substantial credit programs can be used in the betterment of the transport and logistics sector, among other things. The research which merges macroeconomic factors with sector-specific details puts the emphasis on more favourable financing mechanisms to catalyse the exceptional growth in this township and suggests that we look constantly for pathways through complexities of economic development, logistics, and complexities.